2011
DOI: 10.2147/ndt.s19617
|View full text |Cite
|
Sign up to set email alerts
|

The increasing burden of depression

Abstract: Recent epidemiological surveys conducted in general populations have found that the lifetime prevalence of depression is in the range of 10% to 15%. Mood disorders, as defined by the World Mental Health and the Diagnostic and Statistical Manual of Mental Disorders, 4th edition, have a 12-month prevalence which varies from 3% in Japan to over 9% in the US. A recent American survey found the prevalence of current depression to be 9% and the rate of current major depression to be 3.4%. All studies of depressive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
360
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 611 publications
(368 citation statements)
references
References 24 publications
(24 reference statements)
5
360
0
3
Order By: Relevance
“…Total score of this scale ranges from 0 to 63, among which 0 to16, 17 to 29, and 30 to 63 indicate the mild, moderate, and severe depression, respectively (22). BDI is used to screen depression, measure the severity of symptoms, and evaluate the response to the medications and surgery in patients with PD (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). This test has a high internal consistency and test-retest reliability (ICC = 0.93, a = 0.91) (23).…”
Section: Bdimentioning
confidence: 99%
See 1 more Smart Citation
“…Total score of this scale ranges from 0 to 63, among which 0 to16, 17 to 29, and 30 to 63 indicate the mild, moderate, and severe depression, respectively (22). BDI is used to screen depression, measure the severity of symptoms, and evaluate the response to the medications and surgery in patients with PD (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). This test has a high internal consistency and test-retest reliability (ICC = 0.93, a = 0.91) (23).…”
Section: Bdimentioning
confidence: 99%
“…Depression is one of the common non-motor symptoms (about 30% to 40%) with an unknown cause, which has a negative effect on quality of life, functional, and cognitive ability of the patients (4), and can impose a great cost on the health system. Moreover, depression has a high correlation with suicide and is considered as a third reason for disability worldwide (5,6). Therefore, diagnosis of depression in patients with PD could be helpful in their treating and preventing the damages caused by depression.…”
Section: Introductionmentioning
confidence: 99%
“…29 Depression is a pervasive human disorder that affects all spheres of functioning. 30,31 Depression has been shown to impact work performance and well-being. 32 Research on missionary performance has shown anxiety and moodiness as key indicators of performance.…”
Section: Mental Healthmentioning
confidence: 99%
“…Globally, the lifetime prevalence of major depressive disorders was estimated to be between 10% and 15%. 1 may also have had a negative impact on the developing fetus and may have been associated with premature births and lower birth weights. 3,4 Moreover, in a study of a sample of 3,472 pregnant women aged 18 years and older in Michigan, USA, the results showed that 20% (n=689) of the women who were screened, scored above the cutoff score of depression, and only 13.8% of those women reported to have received any formal treatment for depression.…”
Section: Introductionmentioning
confidence: 99%